Reevaluating the Impact of Corporate Governance Mechanisms on Investment Management, Financing Strategies, and Corporate Performance - Yun Tseng, Hsiao; Salam, Niaz A; Kazemi, Mahmud; Nadiheidari, Hasan; Mehlabani, Ehsan Gorjian (Management Analytics and Social Insights, 2024)
This study aimed to propose a model for analyzing the effects of six corporate governance mechanisms (i.e. institutional ownership, management ownership, board ownership, board size, non-executive board members, and CEO duality) on investment management, financing methods, and corporate performance. The statistical population included the companies listed on the Tehran Stock Exchange from March 21, 2012 to March 21, 2019. The systematic sampling method was employed for a case study, and the multiple regression analysis was performed in EViews to test the research hypotheses. According to the results, corporate governance mechanisms had significant relationships with investment management and corporate performance. There were also significant relationships between corporate governance variables (i.e. board ownership, board size, non-executive board members, and CEO duality) and financing methods. In addition, there was an inverse relationship between management ownership and financing methods. Finally, no significant relationship was found between institutional ownership and financing methods.